2015
DOI: 10.1002/sdtp.10110
|View full text |Cite
|
Sign up to set email alerts
|

P‐50: Integrated Gate Drive Circuit Employing IGZO TFTs for AMOLED Compensative Pixel Driving

Abstract: In order to compensate the threshold voltage variation while obtaining the sufficient data charging time, the AMOLED compensative pixel circuit needs to be driven by multi-pulse signals which have continuous high/low level pulses. By using traditional gate driver on array (GOA) with half duty-cycle delay of clock signals, the area of shift register is doubled, increasing the bezel width and power consumptions. In this paper, novel compact integrated gate driver circuit architectures for AMOLED pixel compensati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Small threshold voltage variation of a-IGZO TFTs induced by processes or long-term operation might result in deterioration of the circuits [12], [13]. To address these issues, many circuit designs have been proposed in the past, which, however, increase the circuit complexity and thus the layout area [14]- [17]. Moreover, very few of these designs were realized with large area manufacturing processes, and their functionalities were not verified through standard reliability tests.…”
Section: Introductionmentioning
confidence: 99%
“…Small threshold voltage variation of a-IGZO TFTs induced by processes or long-term operation might result in deterioration of the circuits [12], [13]. To address these issues, many circuit designs have been proposed in the past, which, however, increase the circuit complexity and thus the layout area [14]- [17]. Moreover, very few of these designs were realized with large area manufacturing processes, and their functionalities were not verified through standard reliability tests.…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, the GOAs usually provide only one type of driving signal with a single pulse [4]. For the internal compensation, the pixel circuits require complex driving signals including scan signals [5], and emission control signals [6]. Furthermore, in order to minimize the GOA area, it is preferable to use one set of gate driver to output multiple scan signals and emission control signals, instead of using multiple gate drivers to generate different signals independently [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in order to minimize the GOA area, it is preferable to use one set of gate driver to output multiple scan signals and emission control signals, instead of using multiple gate drivers to generate different signals independently [6], [7]. Previously, a programmable start signal and high-frequency clocks was used to generate multi-pulse signals [5] Yet, only one scan signal is generated in a gate driver unit. Although Kin's circuit enables outputs of scan and emission signals simultaneously [6], the diode-connected structure between bootstrapping nodes (Q nodes) might suffer from insufficient bootstrapping due to charge loss.…”
Section: Introductionmentioning
confidence: 99%
“…The GOA circuit proposed by Li et al can generate single pulses with programmable width [8]. And Cao et al reported a circuit that can produce outputs with programmable pulse width and number [9]. However, neither of the circuits could drive pixel circuit in Figure.1 because they cannot generate the SCAN1 signal, which is commonly used in internal VTH compensated pixel circuits [6] [9].…”
Section: Introductionmentioning
confidence: 99%